Gamificação e aprendizagem: o uso de elementos de jogos como estratégia motivadora na capacitação a distância dos servidores da UFPB - Silva, Marcos Galvão Lourenço da (2021)
This research investigated the applicability of game elements at the learning management system used by the Federal University of Paraíba for it public servant’s distance learning, seeking to identify and apply these concepts in a practical form. It’s overall objective was to develop a course prototype at Moodle, based on gamification principles, to be utilized in training courses avaliable on UFPB. To achieve this objective, the course “Gestão da Comunicação nas Redes Sociais” was reconfigured according the gamification principles and the tools avaliable on Moodle. It’s a research of qualitative, exploratory and applied approach. The methodological procedures applied to create the gamified version of the course it’s the Moodle, open-source software wich contains tools that support the use of gamification. The course selected to the functional prototype it’s “Gestão da Comunicação nas Redes Sociais”, provided by the institution for this research. As result of this research it’s the contribution for a better understanding of theoretical and pratical procedures for the use of game elements in learning management systems, as a way to improve learner’s motivation and engagement.